2020
DOI: 10.3389/fphys.2020.00282
|View full text |Cite
|
Sign up to set email alerts
|

Contractile Behavior of Mouse Aorta Depends on SERCA2 Isoform Distribution: Effects of Replacing SERCA2a by SERCA2b

Abstract: Citation: Fransen P, Chen J, Vangheluwe P and Guns P-J (2020) Contractile Behavior of Mouse Aorta Depends on SERCA2 Isoform Distribution: Effects of Replacing SERCA2a by SERCA2b. Frontiers in Physiology | www.frontiersin.org March 2020 | Volume 11 | Article 282 Fransen et al. Vascular Effects of SERCA2amice, while no difference in potency between strains were observed for acetylcholine. In summary, despite the relative low expression of SERCA2a in the murine aorta, our results point toward a distinct role in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(42 reference statements)
2
3
0
Order By: Relevance
“…In VSMC, Orai1- and STIM1-dependent activation of SOCE can be elicited by stimulation with SERCA pump inhibitor CPA ( Ng et al, 2010 ). In the present study, it was shown that CPA-stimulated aortic rings displayed significant aortic stiffening at low cyclic stretch exposure, specifically in aged mice and independent of eNOS genotype (thereby matching the pattern of Orai1 and STIM1 gene expression reduction) and resembling the CPA effects in mice in which SERCA2a was replaced with SERCA2b ( Fransen et al, 2020 ). Our research group previously showed that SOCE in the healthy mouse aorta is insufficient to elicit significant aortic contractions ( Fransen et al, 2020 ).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In VSMC, Orai1- and STIM1-dependent activation of SOCE can be elicited by stimulation with SERCA pump inhibitor CPA ( Ng et al, 2010 ). In the present study, it was shown that CPA-stimulated aortic rings displayed significant aortic stiffening at low cyclic stretch exposure, specifically in aged mice and independent of eNOS genotype (thereby matching the pattern of Orai1 and STIM1 gene expression reduction) and resembling the CPA effects in mice in which SERCA2a was replaced with SERCA2b ( Fransen et al, 2020 ). Our research group previously showed that SOCE in the healthy mouse aorta is insufficient to elicit significant aortic contractions ( Fransen et al, 2020 ).…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, it was shown that CPA-stimulated aortic rings displayed significant aortic stiffening at low cyclic stretch exposure, specifically in aged mice and independent of eNOS genotype (thereby matching the pattern of Orai1 and STIM1 gene expression reduction) and resembling the CPA effects in mice in which SERCA2a was replaced with SERCA2b ( Fransen et al, 2020 ). Our research group previously showed that SOCE in the healthy mouse aorta is insufficient to elicit significant aortic contractions ( Fransen et al, 2020 ). This indicates that in aged arteries, reorganization of the contractile and/or adhesive apparatus of VSMC results in a higher calcium sensitivity, resulting in active aortic stiffening upon SOCE.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Furthermore, cardiomyocyte Ca 2+ transporter protein expression is altered during HF in humans and animals. Notably, NCX1 and TRPC6 are usually upregulated, and SERCA2a, the predominant sarcoendoplasmic reticulum Ca 2+ pump (SERCA) isoform in the heart ( 494 ), is usually downregulated in HF ( 495 498 ), albeit not always ( 499 ). Since prolonged treatment with low-dose ouabain increases NCX1 expression in rat cardiomyocytes ( Fig.…”
Section: The Physiology and Pathophysiology Of Cts-nka Interactionsmentioning
confidence: 99%
“…Changes of their expression results in cell malignancy, ER-stress and apoptosis [ 5 , 6 ]. Not incidentally, the first recognized task of this pump is to control relaxation in skeletal, cardiac and to some extent in smooth muscle [ 7 ]. Its role in development and differentiation has not been fully highlighted yet but it is supported by the expression of numerous isoforms.…”
Section: Introductionmentioning
confidence: 99%